Anorectal dysfunction in multiple sclerosis patients: A pilot study on the effect of an individualized rehabilitation approach - Kovari, Martina; Stovicek, Jan; Novak, Jakub; Havlickova, Michaela; Mala, Sarka; Busch, Andrew; Kolar, Pavel; Kobesova, Alena (NeuroRehabilitation, 2022)
BACKGROUND: Anorectal dysfunction (ARD), especially bowel incontinence, frequently compromises the quality of life in multiple sclerosis (MS) patients. The effect of rehabilitation procedures has not been clearly established. OBJECTIVE: To determine the effect of an individualized rehabilitation approach on bowel incontinence and anorectal pressures. METHODS: MS patients with ARD underwent 6-months of individually targeted biofeedback rehabilitation. High resolution anorectal manometry (HRAM) and St. Mark's Fecal Incontinence Scores (SMIS) were completed prior to rehabilitation, after 10 weeks of supervised physiotherapy, and after 3 months of self-treatment. RESULTS: Ten patients (50%) completed the study. Repeated measures analysis of variance (ANOVA) demonstrated significant improvement in the SMIS questionnaire over time [14.00 baseline vs. 9.70 after supervised physiotherapy vs. 9.30 after self-treatment (p = 0.005)]. No significant improvements over time were noted in any HRAM readings: maximal pressure [49.85 mmHg baseline vs. 57.60 after supervised physiotherapy vs. 60.88 after self-treatment (p = 0.58)], pressure endurance [36.41 vs. 46.89 vs. 49.95 (p = 0.53)], resting pressure [55.83, vs 52.69 vs. 51.84 (p = 0.704)], or area under the curve [230.0 vs. 520.8 vs. 501.9 (p = 0.16)]. CONCLUSIONS: The proposed individualized rehabilitation program supports a positive overall effect on anorectal dysfunction in MS patients.
Keywords: Manometry; Humans; bowel incontinence; St. Mark’s fecal incontinence score; Multiple Sclerosis; Quality of Life; lidé; kvalita života; Fecal Incontinence; fekální inkontinence; pilotní projekty; Pilot Projects; Multiple sclerosis; roztroušená skleróza; high resolution anorectal manometry; Biofeedback, Psychology; manometrie; biofeedback; biofeedback (psychologie)